Association of FOXE1 polyalanine repeat region with thyroid cancer is dependent on tumour size. (22nd August 2016) - Raimundo, Joana; Alvelos, Maria I.; Azevedo, Teresa; Martins, Teresa; Rodrigues, Fernando J.; Lemos, Manuel C.
Summary: Objective: Polymorphisms in the thyroid transcription factor forkhead factor E1 ( FOXE1 ) gene have been implicated in the genetic susceptibility to differentiated thyroid cancer, but little is known about their effect on tumour characteristics. The objective of this study was to determine the contribution of the FOXE1 polyalanine repeat region to the susceptibility to thyroid cancer and to its clinical characteristics. Design, patients and measurements: A total of 500 patients with sporadic thyroid cancer (440 papillary and 60 follicular thyroid carcinoma) and 502 healthy controls were included in this case–control association study. The number of FOXE1 alanine repeats in each subject was determined by PCR and multiplex fragment analysis by capillary electrophoresis. FOXE1 genotype and allele frequencies among groups were compared by logistic regression and adjusted for sex and age at diagnosis. Data were analysed according to cancer subtype, tumour size and the presence of lymph node or distant metastasis. Results: FOXE1 alleles with 16 or more alanine repeats were more frequent in patients with tumour size > 1 cm compared to tumour size ≤ 1 cm (adjusted OR 1·44; 95% CI 1·05‐1·88; P = 0·019). Genotypes containing at least one allele with 16 or more alanine repeats were associated with larger tumour size (adjusted OR 1·71; 95% CI 1·15‐2·57; P = 0·009). No significant differences were observed between cancer subtypes or the presence/absence of metastasis. Conclusions: FOXE1 polyalanine repeat polymorphisms are associated with thyroid cancer, but only for tumours larger than 1 cm, suggesting a role in disease progression.